A New (–)-5′, 6-dimethoxyisolariciresinol-(3″, 4″-dimethoxy)-3α-O-β-D-glucopyranoside from the bark of Aglaia eximia (Meliaceae). Issue 19 (1st October 2016) - Sianturi, Julinton; Harneti, Desi; Darwati,; Mayanti, Tri; Supratman, Unang; Awang, Khalijah
Abstract: New (–)-5′, 6-dimethoxyisolariciresinol-(3″, 4″-dimethoxy)-3 α - O - β -d -glucopyranoside compound was isolated from the methanol extract of the bark of Aglaia eximia (Meliaceae). The chemical structure of the new compound were elucidated on the basis of spectroscopic data including, UV, IR, HR-ESI-TOFMS, 1D-NMR, 2D-NMR and comparison with those related compounds previously reported. Abstract :